COT-22 TIMING OF SURGERY AND BEVACIZUMAB THERAPY FOR MALIGNANT GLIOMAS. (16th December 2019) - Matsubara, Toshio; Mouri, Genshin; Ishigaki, Tomoki; Ikezawa, Munenari; Suzuki, Hidenori
Abstract: BACKGROUND: The drug manufacturer recommends postponing initiation of bevacizumab for malignant gliomas at least 4 weeks later postoperatively. Malignant glioma patients with significant neurological deficits due to postoperative residual tumors are preferably needed earlier bevacizumab therapy that expecting improvement of neurological state and brain edema. There is a literature review indicating that the timing for administration of postoperative bevacizumab was at least 2 weeks. The authors assessed the safety, tolerability, efficacy for bevacizumab therapy less than 4 weeks later postoperatively. METHODS: Six patients of malignant gliomas with residual tumors and neurological deficits were treated by bevacizumab (10mg /kg every 2 weeks) therapy 2–3 weeks later postoperatively with chemoradiotherapy. Patients included 31-year-old female with thalamic-midbrain glioblastoma (initial), 11-year-old female with anaplastic ependymoma (recurrent), 71-year-old female with initial cervical cord anaplastic astrocytoma (initial), 88-year-old female bilateral frontal glioblastoma (initial), 27-year-old female with thalamic midbrain glioblastoma (initial) and 3-year-old female with brain stem glioblastoma (initial). RESULTS: All the patients did not experienced hemorrhage and impair wound healing. Every patient neurological state and perifocal brain edema following bevacizumab therapy demonstrated early improvement. Earlier bevacizumab therapy did not delay and cease postoperative chemoradiotherapy. CONCLUSIONS: Initiation of bevacizumab therapy 2–3 weeks later postoperatively seems to be safe and effective for malignant glioma patients with worse neurological state due to residual tumor and perifocal edema. The optimal interval which balances the risk of complications and the risk of tumor progression should be considered.